2015
DOI: 10.1007/s11999-015-4526-0
|View full text |Cite
|
Sign up to set email alerts
|

Implant Design Variations in Reverse Total Shoulder Arthroplasty Influence the Required Deltoid Force and Resultant Joint Load

Abstract: Background Reverse total shoulder arthroplasty (RTSA) is widely used; however, the effects of RTSA geometric parameters on joint and muscle loading, which strongly influence implant survivorship and long-term function, are not well understood. By investigating these parameters, it should be possible to objectively optimize RTSA design and implantation technique. Questions/purposes The purposes of this study were to evaluate the effect of RTSA implant design parameters on (1) the deltoid muscle forces required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 32 publications
5
87
1
Order By: Relevance
“…However, a glenosphere of more than half a sphere will allow a lateralization of the center of rotation. This in turn facilitates the function of the remaining rotator cuff [23, 26, 41]. This morphology of the glenosphere determines the lateralization of the center of rotation of the joint.…”
Section: Glenosphere Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a glenosphere of more than half a sphere will allow a lateralization of the center of rotation. This in turn facilitates the function of the remaining rotator cuff [23, 26, 41]. This morphology of the glenosphere determines the lateralization of the center of rotation of the joint.…”
Section: Glenosphere Optionsmentioning
confidence: 99%
“…The thickness of the insert can also differ to help achieve optimal stability and lateralization but one should be careful not to overstuff the joint creating negative effects on deltoid force and joint loading [26]. There is interadaptibility available so that most sizes of humeral components can be combined with most sizes of glenospheres.…”
Section: Polyethylene Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies have used biomechanical models, with cadavers or bone substitutes, to identify relationships between implant design parameters and ROM . In a study utilizing artificial shoulder bones, Gutierrez et al found that increasing lateral offset of the center of rotation increased impingement‐free abduction ROM.…”
mentioning
confidence: 99%
“…In addition, current computational models do not consider the effects of multiple motion‐limiting factors simultaneously. For example, while increasing the center of rotation lateralization decreases impingement, it simultaneously increases the required deltoid force . So, what is the ultimate effect on the comprehensive ROM?…”
mentioning
confidence: 99%